Thermophysical properties of the refrigerant mixtures R410A and R407C from dynamic light scattering (DLS) - Fröba, Andreas Paul; Leipertz, Alfred (International Journal of Thermophysics, 2003)
Dynamic light scattering (DLS) has been used for the measurement of several thermophysical properties of the refrigerant mixtures R410A and R407C. Thermal diffusivity and sound speed have been obtained by light scattering from bulk fluids for both the liquid and vapor phases under saturation conditions over a temperature range from about 290 K up to the liquid-vapor critical point. By applying the method of DLS to a liquid-vapor interface, also called surface light scattering (SLS), the saturated liquid kinematic viscosity and surface tension can be determined simultaneously. These properties have been measured for R410A and R407C from about 240 to 330 K and 240 to 350 K, respectively. The results are discussed in detail in comparison with literature data and with a simple prediction method based on the mass-weighted properties of the pure components expressed as functions of the reduced temperature.
Keywords: dynamic light scattering; kinematic viscosity; R407C; R410A; sound speed; surface light scattering; surface tension; thermal diffusivity